New species of Exochus Gravenhorst and Trieces Townes (Hymenoptera, Ichneumonidae, Metopiinae) and first record of seven species from Brazil - Melo, Ivy Frizo De; Araújo, Carolina Rodrigues; Penteado-Dias, Angélica Maria (Zootaxa, 2015)
Exochus atlanticus sp. n., Melo & Penteado-Dias, and Trieces broadi sp. n., Melo & Penteado-Dias, are described and illustrated in Brazilian fauna. The genus Exochus and the species E. ablatus, E. izbus, T. azipas, T. riodinis, T. wardae, T. upermia and T. wascia, are recorded for the first time from Brazil. Diagnosis and distribution information for each species are provided.